Virilizing Leydig-Sertoli Cell Ovarian Tumor Associated with Endometrioid Carcinoma of the Endometrium in a Postmenopausal Patient: Case Report and General Considerations - Di Giacinto, Paola (Libertas Academica, 2012)
INTRODUCTION: Sertoli-Leydig cell tumors (SLCTs) are rare tumors mostly occurring in young women. Here we report an unusual case of a SLCT with simultaneous occurrence of endometrioid adenocarcinoma of the endometrium in a woman in menopause. CASE REPORT: A 67-year-old woman presented with progressive signs of virilization. Blood tests showed increased levels of testosterone, delta-4-androstenedione, and dehydroepiandrosterone (DHEA). DHEA-sulphate, 17β-estradiol, estrone, and sex-hormone binding globulin serum levels were within the normal range. Magnetic resonance imaging revealed a solid mass of 2.7 × 2.9 cm in the right ovary set against the background of the uterus. The patient underwent bilateral salpingo-oophoretomy with hysterectomy. The mass in the right ovary was a differentiated SLCT. Incidentally, the endometrium revealed an endometrioid adenocacinoma. Following surgical treatment the plasma androgens dropped to normal levels, and signs and symptoms of virilization improved. CONCLUSION: SLCT should be suspected in postmenopausal women who present rapid progressive androgen excess symptoms with hyperandrogenemia.